MOLUSCOS Y SU TAXOCENOSIS EN LOS FONDOS SOMEROS DEL SECTOR SUR DE LA PLATAFORMA CONTINENTAL DEL CARIBE COLOMBIANO (Boletín de Investigaciones Marinas y Costeras, 2016)
During a baseline survey of the shallow bottoms (10-50 m) of the southern continental shelf  of the Colombian Caribbean, a total of 35 molluscan species belonging to 24 families was collected. Three main molluscan bottom assemblages were recognized according to species composition and abundance, whose distribution seems likely to be controlled rather by depth than by sediment features. Twenty four of the species were not recorded before from this area of the Colombian Caribbean.